STRATEGY OF EDUCATION QUALITY IMPROVEMENT ON SENIOR HIGH SCHOOL ARGOPURO PANTI - Syaeful Al-Hamzah; Muhammad Firdaus; Zainollah (MBA - Journal of Management and Business Aplication, 2021)
Quality of education is one of the central isue of national education among other isues such asequlization, relevance and educational management eficiencies. SMA Argopuro Panti is stillfaced with several obstacles that affect the quality of education, which regard to the backgroundof students and their families, support of educational resources, teachers qualification, and lowcommunity participation. This research aims to obtain information about the policies underlyingthe school-based education quality improvement program, and how the school stakeholdersunderstanding of the policy and to analyze information about alternative strategies for improvingthe quality of schoole-based education, regarding to the education program in SMA ArgopuroPanti Jember. Informants in this study are founders of foundations, school committee members,and teacher, research subjects are relatively few and selected according to the research objects. Inthis study, collection uses snowball sampling techniques. Data analysis method uses SWOTanalysis method. Based on the results of the analysis it is known that SMA Argopuro Panti is in avery favorable situation, it should able to compete because according to data analysis this schoolalready has the strengthand opportuintyto improve its quality and dare to compete with otherschools. The strategy applied in this condition is to support an aggressive growth policy growthoriented strategy.Keywords : Strategy, Development, Quality of Education